Considerations Regarding the Role of Attitude and Behaviour in the Development of Motion Thorough Physical Activity - Andrei, Vasile Liviu (Arena-Journal of Physical Activities, 2017)
This Â article Â draws Â the Â attention Â of Â important Â considerations Â regarding Â the creation, development, promotion and support for the cult of moving exer- cise in human life, from the earliest age until old age. There are shown here relevant aspects of educational factors in connection with their involvement in the development of the sports movement, contents and forms of exercise, extending it to the mass phenomenon.There are proposed certain ways of addressing to the physical exercise, train- ing the most important stakeholders in the development of this cult, given the Â need Â for Â individual Â and Â social Â health, Â performance Â and Â Olympic Â spirit in sports, recognition and appreciation of the nation and the country among civilized world.